Commercial Imperialism? Political Influence and Trade During the Cold War - Berger, Daniel; Easterly, William; Nunn, Nathan; Satyanath, Shanker (American Economic Review, 2013)
We provide evidence that increased political influence, arising from CIA interventions during the Cold War, was used to create a larger foreign market for American products. Following CIA interventions, imports from the US increased dramatically, while total exports to the US were unaffected. The surge in imports was concentrated in industries in which the US had a comparative disadvantage, not a comparative advantage. Our analysis is able to rule out decreased trade costs, changing political ideology, and an increase in US loans and grants as alternative explanations. We provide evidence that the increased imports arose through direct purchases of American products by foreign governments. (JEL D72, F14, F54, N42, N72)